Experimental study on performance of waste autoclaved blocks and coal gangue in coal mine goaf ground grouting improvement - Lianwei REN; Bo LI; Youfeng ZOU; Zhilin DUN; Wenfu YANG (Meitan kexue jishu, 2023)
With the development of society, a large number of waste autoclaved blocks and gangue on the surrounding environment, in order to protect the environment and reuse resources, these solid wastes have been effectively utilized in the field of grouting reinforcement. This article using waste autoclaved aerated concrete block and waste coal gangue as two kinds of solid waste as the main materials, and mixed with cement to make two kinds of grouting slurry used as goaf foundation treatment and filling, solve the problem of solid waste used in grouting materials resource utilization, realize the transformation of waste into treasure. The test adopted the mixing ratio method, and finally selected the grouting slurry with the most suitable ratio in the aspects of setting time, viscosity, water evolution rate and stone rate, liquidity and compressive strength. The results show that the setting time, viscosity, water extraction rate and stone rate of each WAACBP-cement grout are all in line with the grouting grout standards for goaf foundation treatment, but only 50% and 60% quality replacement rates can be selected for the compressive strength standards. WCGP−cement grout 70% and 80% of the grout in water evolution rate, stone rate and compressive strength do not meet the standard, so can only choose 50% and 60% of the grout ratio, the two kinds of grout in economic perspective analysis, the final selection of 60% of the grout ratio. Finally, performance of the setting time, viscosity, water evolution rate, stone rate, liquidity and compressive strength of the two kinds of grout analyzing, the most suitable grout is WCGP−cement grout.